2015
DOI: 10.1016/j.semnephrol.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus in Kidney Disease

Abstract: Summary Pruritus is a common and distressing symptom in patients with chronic kidney disease. The most recent epidemiologic data have suggested that approximately 40% of patients with end-stage renal disease experience moderate to severe pruritus and that uremic pruritus (UP) has a major clinical impact, being associated strongly with poor quality of life, impaired sleep, depression, and increased mortality. The pathogenesis of UP remains largely unclear, although several theories on etiologic or contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 70 publications
4
106
2
7
Order By: Relevance
“…4 It has been postulated that creams that rehydrate dry skin (emollients) may improve itching. 71 Several different formulations of emollient creams have been studied in patients with CKD-aP.…”
Section: Xerosis Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4 It has been postulated that creams that rehydrate dry skin (emollients) may improve itching. 71 Several different formulations of emollient creams have been studied in patients with CKD-aP.…”
Section: Xerosis Treatmentmentioning
confidence: 99%
“…72 Several additional non-controlled trials have also shown the beneficial effects of compounds containing emollient creams in patients with xerosis and CKD-aP. 71,[73][74][75][76] In a prospective clinical trial, 200 g of a aqueous cream applied twice daily significantly improved pruritus severity in 16 out of 21 recruited dialysis patients and resulted in the abatement of itching in 9 patients. 75 In a prospective study of 21 HD patients, all treated with structured physiological lipids and endogenous cannabinoids twice daily for 3 weeks, pruritus severity was significantly reduced at the end of the treatment period and pruritus completely abated in 8 of 21 participants.…”
Section: Xerosis Treatmentmentioning
confidence: 99%
“…They are not recommended in recent reviews. 71,72 Crucially, a recent functional magnetic resonance imaging study revealed that in uremic pruritis, the central transmission of itch is via a non-histaminergic pruritus pathway and not a histaminergic pathway. 85 These medications have sedating effects, which are especially risky in the older and frailer ESRD population.…”
Section: Uremic Pruritusmentioning
confidence: 99%
“…7274,77–80,82,8593,95,96 BUN, blood urea nitrogen; GFR, glomerular filtration rate; PTH, parathyroid hormone; UP, uremic pruritus.…”
Section: Figurementioning
confidence: 99%
“…Various pathophysiological mechanisms for UP have been proposed in recent years, including hypervitaminosis A, skin xerosis, hyperparathyroidism, histamine binding to the H4 receptor, iron deficiency, elevated levels of histamine, homeostasis unbalance in phosphate, magnesium and calcium [7]. It is also identified to be a complex condition whereby opioids, mast cells, elevated skin surface pH and some components in dialysis membranes are recognized as pathogen for UP [8].…”
Section: Introductionmentioning
confidence: 99%